APPLICATION STRATEGY OF SMART FARMING TECHNOLOGY 4.0 IN UTILIZING RITX SOIL AND WEATHER SENSOR - Lina Asnamawati; Timbul Rasoki; Is Eka Herawati; Ana Nurmalia; Siti Suharsih (JURNAL AGRIBISNIS TERPADU, 2022)
Research design is predictive and descriptive involving several concepts. Partial least squares, research and development tests are used in developing the application of smart farming technology. The results analysis prove the direct influence of variables X_1 (genetic factors) to Y_1 (farmer behavior in the application smart farming) of -0.269. It show does not have a positive impact on the contrary reducing the behavior of farmers in implementing smart farming. The relationship between X_2 (individual external factors) to Y_1 is 0.392 show that individual external factors give positive impact on increasing farmer behavior in the application of smart farming by 39.2%.